Morphological Evaluationof Tomato (Solanum lycopersicumLinn.) Cultivars - Chime, Anthonia Odinita; Aiwansoba, Raymond Osas; Osawaru, Moses Edwin; Ogwu, Matthew Chidozie (UI Scholars Hub, 2017)
Tomato (Solanum lycopersicumLinn.) is widely cultivated andis economically beneficial. Tomatocultivars were obtained from traditional agriculture systems, and their morphological characters were evaluated. The cultivars included Pepper tomato [ED/CH/01], Edo local [ED/CH/02], Golden tomato [ED/CH/03]and Derica tomato [ED/CH/04]. Results of the principal component analyses of 27 morphological characters indicated that two characters accounted for 94.65 % of the observed variations. Scatter plots suggested good tendency of grouping for the four accessions. In the dendrogram, two clusters were formed withED/CH/01, ED/CH/02 and ED/CH/03 grouped together whereas ED/CH/04 clustered separately.The clustering pattern implicated a common origin and/or gene pool for the cultivars. Cultivars ED/CH/01, ED/CH/03 and ED/CH/04 showed determinate growth type, while ED/CH/02 showed a semi-determinate growth pattern. Further, in terms of plant size, ED/CH/01 and ED/CH/02 were intermediate, while ED/CH/03 and ED/CH/04 were large. The characteristics of the flower and fruits exhibited diversity in terms of the corolla color, style, shape, fruit size at maturity, exterior color of the mature fruit, fruit shoulder, fruit cross-sectional shape, and fruitblossom end shape. These cultivars collectively possess characteristics that can be used by plant breeders. Werecommend that further characterization using molecular techniques as well as conservation attention for these local germplasms should be conducted.